The Use of Animated Video Media in Teaching Fairy Tales to Lower Grade Students at MI Ma’arif NU 01 Kajongan - Rahma, Annisa Auwla; Suharto, Abdul Wachid Bambang (IJLHE: International Journal of Language, Humanities, and Education, 2025)
The use of fairy tale materials in Indonesian language instruction is aimed at achieving predetermined competency standards. To meet these standards, a solid understanding of theoretical concepts is essential. In order to minimize misunderstandings in the delivery of theoretical content, the use of appropriate instructional media is necessary. This study aims to describe the implementation of animated video media in teaching fairy tale content to lower grade students. Employing a qualitative research method with a case study approach, the study was conducted at MI Ma’arif NU 01 Kajongan. Data were collected through observation, interviews, and documentation. Data analysis was carried out using an interactive model comprising data reduction, data display, and conclusion drawing. The findings indicate that teachers are able to integrate animated video media effectively in the instruction of fairy tales by adhering to key principles of media utilization during the planning, implementation, and evaluation phases. These findings imply that incorporating engaging multimedia resources can enhance young learners’ comprehension and motivation in language learning.